Peranan Galeri Investasi Bursa Efek Indonesia Selama Masa Pandemi Covid-19 Dalam Meningkatkan Jumlah Investor - Simamora, Klarita Pitrusani Octavia; Rosdianti, Novi; Mardiana, Elida (CV. ITTC INDONESIA, 2023)
Many industries have been affected by Covid-19 due to investors who are hesitant to invest. This was shown based on data from the Indonesian Stock Exchange, which experienced a decline in the Jakarta Composite Index (IHSG) at the start of the pandemic, namely in the first quarter of 2020. But in the second quarter of 2020 (May 2020-June 2020) it showed an increase. This is a success in the role of the Indonesian Stock Exchange Investment Gallery to become one of the records in the history of the Indonesian Capital Market. This study aims to determine the role of the Indonesian Stock Exchange Investment Gallery in increasing the number of stock investors in the Indonesian Capital Market. The research method used is descriptive qualitative with data sources in the form of secondary data from journals and previous scientific articles. The data collection technique used is literature and literature study. The conclusion in this study is that the success of investment galleries is influenced by internet penetration, the distribution of domestic investors, the number of investment galleries and their role which is right on target in Generation Z.